Water Infiltration, Resistance to Penetration and Soil Moisture in Integrated Agricultural Yield Systems over Time. Issue 3 (4th February 2022) - Lozano Olivério, Gabriela; dos Santos Batista Bonini, Carolina; Fernanda Dias Souza, Jéssica; Luís Sanchez Perusso, Rafael; Meirelles, Guilherme Constantino; Andrighetto, Cristiana; Carlos Lupatini, Gelci; Pavan Mateus, Gustavo; Lapaz, Allan de Marcos; Heinrichs, Reges; Moreira, Adônis
ABSTRACT: Soil conservation systems can achieve agricultural sustainability together with the integration and diversification of management activities, exploring the synergism of the system. The objective of this work was to evaluate in a temporal manner the physical attributes of the soil, under a crop-livestock-forest integration system, to verify possible contributions physical quality of the soil and system sustainability itself. The soil under study is a Typical Ultisol. The randomized block design was distributed in four respective treatments: crop-livestock integration, without the tree component (CLI), agrosilvipastoral system, with one eucalyptus ( Eucalyptus ssp.) line of shading (AS1L), agrosilvipastoral system, with three eucalyptus lines of shading (AS3L), and exclusive culture of eucalyptus. The samples were collected from 2014 to 2018, in the 0–0.05, 0.05–0.1, and 0.1–0.2 m layers, to the water infiltration evaluations in soil, resistance to penetration, content of soil humidity. The results revealed that the systems that use integration improve or maintain physical quality of the soil, without compacting or negatively influencing water infiltration, highlighting the treatments CLI, AS1L e AS3L through time, which promotes its sustainability.